(untitled) (Revista de Ciências Agroveterinárias, 2009)
Copro-necrophagous beetles were collected in natural field and forest areas utilizing pitfall traps baited with cattle dung and bovine liver in decomposition, during October of 2007, in Bagé, Rio Grande do Sul, Brazil. The most frequent species were Canthon rutilans (131 individuals) and Ateuchus robustus (39 individuals). The greater number of species and individuals was collected in the forest area. However, the field area presented larger diversity index than the forest area. The ecosystem type has a pronounced effect on the assemblage composition of the Scarabaeidae. Eurysternus navajasi is a new specie registered in Bagé.